Nanofibered Gelatin‐Based Nonwoven Elasticity Promotes Epithelial Histogenesis. Issue 10 (12th March 2018) - Jedrusik, Nicole; Meyen, Christoph; Finkenzeller, Günter; Stark, G. Björn; Meskath, Stephan; Schulz, Simon Daniel; Steinberg, Thorsten; Eberwein, Philipp; Strassburg, Sandra; Tomakidi, Pascal
Abstract: Regarding tissue regeneration, mechanics of biomaterials gains progressive importance. Therefore, this study reports on in situ crosslinked electrospun gelatin nonwoven mats (NWMs) whose distinct modulus of elasticity (ME) promotes epithelial tissue formation in a graded manner. NWMs, comprising fiber diameters in various distributions, yield an ME of about 2.1, 3.2, and 10.9 kPa. A two‐step approach of preclinical in vitro validation identifies the elasticity of 3.2 kPa as superior to the other, regarding the histogenetic epithelial outcome. Hence, this 3.2 kPa candidate NWM is colonized with oral mucosal epithelial keratinocytes in the absence or presence of mesenchymal fibroblasts and/or endothelial cells. Evaluation of epithelial histogenesis at days 1 to 10 occurs by colorimetric and fluorescence‐based immunohistochemistry (IHCH) of specific biomarkers. These include cytokeratins (CK) 14, CK1, and involucrin that indicate different stages of epithelial differentiation, as well as the basement membrane constituent collagen type IV and Ki‐67 as a proliferation marker. Intriguingly, histogenesis and IHCH reveal the best resemblance of the native epithelium by the NWM alone, irrespective of other cell counterparts. These findings prove the gelatin NWM a convenient cell matrix, and evidence that NWM mechanics is important to promote epithelial histogenesis in view of prospective clinical applications. Abstract : Biomechanical properties influence cell and tissue behavior and consequently biomaterial success in the context of tissue regeneration. Modulus of elasticity of 3.2 kPa of in situ crosslinked gelatin nonwoven mats supports epithelial tissue formation, regarding stratification and differentiation, with no need of in vivo mesenchymal cell counterparts. This novel finding supports the efficient design of biomaterials for adjusted tissue engineering.